Strategi Komunikasi Televisi Lokal dalam Program Dakwah Islami untuk Meningkatkan Engagement Pemirsa - Gilang Saputra; Mahya Chilyatullubab; Mukhlizar (Journal of Communication and Social Sciences, 2026)
This study aims to analyze the communication strategies employed by local television stations in Islamic da’wah programs to increase audience engagement, including program planning, message development, communicator selection, digital media utilization, and supporting and inhibiting factors. This study employed a qualitative approach with a case study design. Informants were purposively selected from television managers, producers, creative team members, Islamic preachers, social media managers, and active viewers. Data were collected through in-depth interviews, observation, and documentation and analyzed thematically through data condensation, coding, theme development, data presentation, and conclusion drawing. Data credibility was ensured through source and technique triangulation, member checking, and persistent observation. The findings generated five main themes: audience-oriented program planning, preacher credibility and message contextualization, interactive audiovisual formats, multiplatform convergence, and engagement evaluation and organizational barriers. Communication strategies integrating local proximity, message relevance, audiovisual creativity, interactivity, and digital distribution were found to foster viewers’ cognitive, emotional, and behavioral engagement. This study concludes that audience engagement should not be measured solely through viewing figures or digital interactions but also through audience understanding, trust, participation, and loyalty. Local television stations should, therefore, adopt audience-centered and multiplatform program management, strengthen data-based evaluation, and maintain Islamic communication ethics in developing sustainable da’wah programs.